How Do Climate and Nonclimatic Variables Influence the Production of Agricultural Staple Crops in Vulnerable Rural Communities in the Bawku Municipality of Northern Ghana? - Rashida Ayumah; Felix Asante; Lawrence Guodaar; Gabriel Eshun (Advances in Agriculture)
We examined the influence of climate (temperature and rainfall) and nonclimatic variables (soil fertility using soil pH and organic matter) on the production of agricultural staple crops (maize [Zea mays L.], millet [Pennisetum glaucum L.], and rice [Oryza sativa L.]) in vulnerable communities in the Bawku Municipality of northern Ghana. Using five selected farming communities as study sites, multiple datasets were obtained from primary and secondary sources. Participatory approaches together with questionnaires were used as data collection tools to quantify and qualify climate (temperature and rainfall) and nonclimatic variables (soil fertility using soil pH and organic matter) and crop production. The Mann–Kendall trend test results indicate a significant variation in annual rainfall for the 15-year period (1999 to 2013) with a relatively stable mean temperature variation in the Municipality. The results of the multiple regression indicate that climatic and nonclimatic factors, particularly rainfall, soil pH, and organic matter have a significant positive effect on maize, millet, and rice when other factors are held constant. We conclude that to ease the burden of climate on production, better irrigation facilities be provided for the Municipality and weather forecasting information on the pending growing season be made available to farmers to enable them take informed decision. Also, policy on climate adaptation should take into account the interaction of external drivers of climate and nonclimatic variables to better build farmers’ resilience for food security at the local level.